(untitled) (UUM Journal of Legal Studies, 2023)
The widespread Covid-19 pandemic has significantly impacted business and commerce across the globe, including Malaysia. As a result, businesses throughout Malaysia may face the inability to perform their contractual obligations and may seek to determine whether they or their counterparty have any legal basis for the non-performance of those contractual obligations. This research used content analysis by categorizing the same theme and discussing the wording adopted in Temporary Measures for Reducing the Impact of Coronavirus Disease 2019 (COVID-19) Act 2020, force majeure clause, and the doctrine of frustration in Malaysia. The Temporary Measures for Reducing the Impact of Coronavirus Disease 2019 (COVID-19) Act 2020 is one of the defenses available to excuse the non-performance of contractual obligations due to Covid-19. However, the Covid-19 act is relatively new, and no precedent has been established to interpret the vague language adopted in the act. It was found that financial hardship can be a ground for non-performance of contractual obligations. Alternatively, contractual parties may invoke the force majeure clause that is provided in a contract. However, the ability to seek relief for force majeure events depends on the precise wording adopted in the clause. In the absence of a force majeure clause, the contractual parties may consider the doctrine of frustration. However, frustration is not a straightforward doctrine to reckon with. This research will provide insight into contractual parties on their rights, remedies, and repercussions if they choose to terminate the contract due to the widespread Covid-19 pandemic.